Treatment of maxillofacial congenital melanocytic nevus with percutaneous radiofrequency thermal ablation: A case series study. Issue 2 (21st February 2021) - Wang, Xinglin; Chen, Wei; Xie, Huimin; Jiang, Tianyu; Weng, Changshui; Zhang, Zhao; Lin, Xisheng; Gao, Yueming
Abstract: When congenital melanocytic nevus (CMN) is in the maxillofacial region, a safer, more effective and fewer side‐effects treatment is needed for patients with high requirement for appearance. The objective of this study was to investigate the effectiveness of radiofrequency thermal ablation (RFA) for CMN in the maxillofacial region. We reviewed 21 patients treated with RFA for CMN followed by a blinded retrospective analysis of serial photographs taken during the course of their therapy. Questionnaires were used to evaluate perceived therapeutic response and complications of this treatment. Most CMNs stopped growing, faded in color and became smaller. Reduction in size of 90% to 100% was obtained in two patients (10%), 75% to 90% in six patients (29%), 50% to 75% in two patients (10%), <50% in eight patients (38%), and three had no reduction (13%). Clear effect of clinical response score was obtained in two patients (10%), excellent in four patients (19%), good in 14 patients (67%), and fair in one patient (4%). No serious complication, severe hypertrophic scarring, and evidence of recurrence was observed in any case. Percutaneous RFA, as a minimally invasive and safe treatment, may provide an alternative treatment for maxillofacial CMN.